2020
DOI: 10.1101/2020.03.31.20042333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of 2019 novel coronavirus in semen and testicular biopsy specimen of COVID-19 patients

Abstract: Background: As of March 11, 2020, the COVID-19 outbreak was declared as a pandemic. Expending our understanding of the transmission routes of the viral infection is crucial in controlling the outbreak. It is unclear whether the 2019 novel coronavirus (2019-nCoV) can directly infect the testes or male genital tract and be sexually transmitted from males. Methods: From January 31 to March 14, 2020, 12 patients in recovery and one patient died of COVID-19 were included in this descriptive study. The clinical char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 22 publications
1
45
1
5
Order By: Relevance
“…ACE2 is not only found in the lungs resulting in respiratory symptoms and lung injury of the SARS-CoV2, but also in many other organs including kidneys, prostate and intestines, suggesting other possible routes of viral transmission, and testes, hence possibly requiring a long-term follow-up of the reproductive function in males. While some authors reported the absence of SARS-CoV2 in the semen of males recovering from COVID-19 [5], others have shown its presence in the semen of active and recovering patients. [6].…”
Section: Mots Clésmentioning
confidence: 99%
“…ACE2 is not only found in the lungs resulting in respiratory symptoms and lung injury of the SARS-CoV2, but also in many other organs including kidneys, prostate and intestines, suggesting other possible routes of viral transmission, and testes, hence possibly requiring a long-term follow-up of the reproductive function in males. While some authors reported the absence of SARS-CoV2 in the semen of males recovering from COVID-19 [5], others have shown its presence in the semen of active and recovering patients. [6].…”
Section: Mots Clésmentioning
confidence: 99%
“…In a recent study, Song et al (2020) collected 12 semen samples from survived COVID‐19 patients and testicular biopsies from a dead COVID‐19 patient. In the semen samples and in testicular biopsy, tissues were not detected 2019‐nCov RNA.…”
Section: Figurementioning
confidence: 99%
“…18 A study on 12 COVID-19 patients demonstrated the absence of viral RNA in testicular biopsy tissues. 103 It indicates that SARS-CoV-2 cannot directly infect testes or the male genital tract even in the acute phase; therefore, no evidence shows that the novel coronavirus can be sexually transmitted from males. 103 Other studies indicated that serum LH in males with COVID-19 infection could be significantly increased; however, the ratio of T to LH and the ratio of follicle-stimulating hormone (FSH) to LH are dramatically decreased.…”
Section: Reproductive System Manifestationsmentioning
confidence: 99%